Generalized edema as the dominant clinical symptom of celiac crisis - Dominika Wilczyńska; Martyna Rekowska; Dorota Lewandowska; Joanna Wyrębska-Ruge; Aneta Krogulska; Anna Szaflarska-Popławska (Termedia Publishing House, 2021)
Celiac disease (celiac disease) is an autoimmune systemic disease caused by the consumption of gluten in genetically predisposed individuals. It is estimated that the incidence of celiac disease is constantly increasing and currently it is seen in 1% of the pediatric population. According to the latest classification, there are classic, non-classical, subclinical and potential forms of celiac disease. In this publication, we present the rare form of celiac disease, which is the classic form in a 2-year-old boy. In children with classic celiac disease the most common clinical picture is chronic diarrhea, abdominal pain, impaired physical development and enlarged abdominal circumference. In the presented patient, the clinical picture was dominated by rapidly increasing edema and laboratory tests showed abnormalities - hypoalbulinemia, ionic disturbances, anemia and disorders of the coagulation system. In a child with generalized edema the differential diagnosis should include the classic form of celiac disease.